IMPLEMENTASI BOARD CARD GAME PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS 5 SEKOLAH DASAR NEGERI 5 SIDOHARJO KABUPATEN WONOGIRI - Prasetyani, Nur; Anggraeni Siwi, Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of Board Card Game media in Indonesian language learning for fifth-grade students at SD Negeri 5 Sidoharjo, Wonogiri Regency. The research was motivated by the low level of student engagement and participation during Indonesian language learning, which was still dominated by conventional teaching methods. This study employed a qualitative descriptive approach involving one classroom teacher and 13 fifth-grade students as research subjects. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman interactive analysis model consisting of data reduction, data presentation, and conclusion drawing. Data validity was tested through source triangulation and technique triangulation. The results showed that the implementation of Board Card Game media was able to create a more active, interactive, and enjoyable learning atmosphere. Students demonstrated increased enthusiasm, participation, cooperation, and confidence in expressing opinions during the learning process. In addition, the use of game-based learning media helped students understand Indonesian language materials more easily through collaborative and student-centered activities. Although several obstacles were found, such as classroom conditions becoming noisier and limited learning time, these challenges could be addressed through effective classroom management by the teacher. Therefore, Board Card Game media can serve as an innovative and effective learning alternative to improve student engagement and learning experiences in Indonesian language learning at the elementary school level.Keywords: Board Card Game, Indonesian language learning, elementary school, learning media, student engagement.